Creating informed consumers: Tracking financial literacy programs in Indonesia - Ajisatria Suleiman; Thomas Dewaranu; Noor Halimah Anjani (Center for Indonesian Policy Studies (CIPS), 2022)
Despite Indonesian consumers taking up and purchasing financial products on various new fintech platforms and services, financial literacy still remains low. This is a risk that is in urgent need of attention as ill-informed financial decisions lead to unmanageable debt and falling victim to illegal investment products. In the long term, these risks can damage consumer trust and broad perception towards financial technologies, which leads to challenges in seeking growth in the sector. This paper will explore how regulators could boost financial literacy and provide consumers with the necessary understanding and knowledge of financial products and personal money management.
Keywords: 330